Perspectives on healthy aging in middle age: Evidence for health promotion interventions - Mahnaz Solhi; Razieh Pirouzeh; Nasibeh Zanjari (Wolters Kluwer Medknow Publications, 2022)
CONTEXT: Understanding how middle-aged people perceive healthy aging and what they need to do to stay healthy as they age can help public policy planning to enhance the lifestyles of middle-aged and elderly people. AIMS: The purpose of this study was to clarify the concept of healthy aging and strategies to achieve it from the perspective of middle-aged people in Tehran, Iran. SETTING AND DESIGN: This qualitative study was performed on 21 middle-aged people aged 45-59 years of Tehran in 2019. SUBJECTS AND METHODS: The data collection was carried out through semi-structured and in-depth interviews; the interviews were audiotaped, transcribed. Sampling was carried out gradually until data saturation through purposive sampling was achieved. STATISTICAL ANALYSIS USED: Data collection and analysis were performed simultaneously. Data were analyzed using conventional content analysis. To establish the reliability and validity of findings, Graneheim and Landman criteria were considered. RESULTS: The middle-aged perspective on healthy aging was included in four main themes: having good physical and mental health, having financial well-being, having social support. Strategies for achieving healthy aging were included in five themes: future financial planning, promoting physical health, promoting psychological health, maintaining and improving communication. CONCLUSION: From the middle-aged perspective, healthy aging and strategies to achieve it are multidimensional. Planning for promotional interventions to have a healthy old age should be including all dimensions and done from the years before old age.